Artistic practice in Waldorf teacher education: a sensory-aesthetic concept for a digital age - Lutzker, Peter (Frontiers in Education, 2024)
One of the general concepts underlying Waldorf education is that teaching is an art. Although this idea is certainly not unique to Waldorf education, what is unique is the way it has been integrated into Waldorf teacher education. While Waldorf teacher education programs are diverse, both in national and international contexts, one of the central elements which they share is the prominent role which different forms of artistic practice play throughout the course of pre-service and in-service programs. This article explores the reasons and aims behind the inclusion of subjects such as music, sculpture, and speech in Waldorf teacher education, at first within the larger context of viewing different perspectives and justifications for the inclusion of the arts in teacher education outside of Waldorf pedagogy. In the final discussion, an argument is made for a broader conceptual basis for the inclusion of the arts in teacher education based on the concept of aesthesis, from the Ancient Greek concept of aisthésis, understood here as the primary perceptual-sensory basis of aesthetic experience. In considering the educational challenges posed by widespread sensory deficits among children and adolescents, viewed here as being connected to the extensive role/s which different forms of digital media play in their lives, the case is made for the potentials of sensory-aesthetic experience as a way to address those deficits. The integration of scientific courses with artsbased studies in teacher education is seen as providing a fruitful basis for teachers to be able to take on these challenges.